Guided Inquiry laboratory-based learning to improve science learning outcomes of VII students at SMPN 2 Tanjung Mutiara School. - Annisa Mardhatillah; Widia Kemala Sari; Fatma Wati; Azza Nuzullah Putri (Pendidikan IPA, FMIPA, UNP, 2026)
This study aims to examine the effect of a practicum-based Guided Inquiry learning model on the science learning outcomes of seventh-grade students on the topic of substances and their changes. The research employed a quasi-experimental method using a pretest posttest nonequivalent control group design. The participants consisted of two classes, namely an experimental class and a control class, each comprising 30 students. Data were collected using a validated objective test and analyzed through descriptive statistics, prerequisite tests, and hypothesis testing using an independent samples t-test at a significance level of 0.05. The results indicated that the initial abilities of students in both groups were relatively equivalent. Hypothesis testing on posttest data revealed a significant difference in learning outcomes between the experimental and control classes, with a t-value of 4.338 exceeding the t-table value of 2.0017 (α = 0.05), indicating that the practicum-based Guided Inquiry learning model had a significant positive effect on students’ learning outcomes. Furthermore, analysis of learning objective achievement showed that TP 3, which focuses on identifying physical and chemical changes through practicum activities, achieved the highest level of mastery compared to other learning objectives. These findings suggest that the practicum-based Guided Inquiry learning model is effective in improving students’ science learning outcomes.